SUSPICIOUS FINANCIAL TRANSACTIONS FROM NARCOTIC TRADING RESULT AS ORIGIN CRIMINAL MEASURES IN MONEY LAUNDERING - Ginting, Yuni Priskila (Veteran Law Review, 2020)
This study examines problem of Illegal drug use supports the legal business activities with the modus of transfering to and hiding the property obtained through a criminal in a legal institution and do the money laundering through a finance institution that the property is regarded being legal. In fact money laundering not always gradually, but rather be combined the stages then do the step over and over that involves manyparties and institutes that provides goods and services. It has to be proven that the prepetrator knows or should suspect the predicate crimes and whether or not double criminality principle fulfilled.The author discusses the authority of the National Narcotics Agency related to the money laundering carried out by criminal suspects narcotics, And cooperation conducted by the National Narcotics Agency with the Center for Financial Transaction Reports Analysis related to the prevention and eradication of money laundering. Modus of money laundering  can be classified into three types of typology such as placement, layering, and integration. Elements of criminal acts are assets and the subject was person, bank, and law enforcement.